THEORY OF EVIDENCE IN THE CIVIL JUDICIARY: MODERN LEGAL MEASUREMENT - Симбірська, Єлизавета Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Aim: to consider the theory and practice of proof in the civil process. Give an analysis of the views of prominent scholars in civil law regarding this category. An assessment of the current state of development of this topic in civil law is given. The vectors of development of this category in modern civil rights will be determined. Methods: the study was conducted using classical methods of scientific knowledge. Using the method of analysis, the system elements of the theory of proof are revealed. Using the method of synthesis, the problematic aspects of scientific and practical support of providing evidence in the civil process are considered. Results: based on the results of the study, the main elements of the theory of proof were determined, the basis for further research in this field was formed. Identified and disclosed components of evidence in the civil process. In modern scientific works, several different approaches to the definition of the concept of proof in civil judicial proceedings are formulated: 1) as a procedural activity of the court and persons involved in the case. The advocates of this approach call evidentiary activity, which forms a dynamic process of identifying, collecting, researching and evaluating evidence that allows the establishment of facts and circumstances relevant to the resolution of the merits of a court case; the logical and practical activity of the persons involved in the case and, to a certain extent, the court, aimed at obtaining the correct knowledge about the actual circumstances of the emergence, change and termination of legal relations, which is carried out in the procedural form by the statement of the persons involved in the case, the facts, legal indications, indication of evidence, the provision of their court, the execution by the court of assistance to those involved in the case, the gathering of evidence, the study and evaluation of evidence; 2) as a procedural activity of the persons involved in the case. Researchers who share this view consider the judicial proof of the activity of those interested in solving cases of persons (parties, applicants, third parties) in the conviction of the court examining the case, in the presence or absence of the legal validity of the facts that substantiate their claims or objections; 3) as a kind of judicial knowledge, which includes both indirect and direct knowledge of the facts of reality, combines cognitive and procedural elements and during which, in accordance with the rules of law, the factual circumstances that are relevant for the correct and timely consideration and resolution of civil cases. An ambiguous assessment of the content, purpose and subject structure of judicial evidence in modern science of civil procedural law allows us to state the need for a thorough investigation of the problem under consideration. First of all, it should be noted that the evidence has clear legal regulation, which manifests itself in a combination of procedural and substantive sources. The procedural law establishes the general provisions on evidence and the procedure of proof: defines the rights and obligations of the participants of the evidence, establishes the requirements for evidence, defines the sequence and content of procedural actions. In addition, the provisions of the principles of civil procedural law: equality of persons involved in the case, before the law and the court (Article 5), the competition of the parties (Article 10), dispositiveness of civil proceedings (Article 11), language civil proceedings (Article 7 of the CPC), other principles of civil procedural law. The rules of substantive law, which regulate controversial legal relations, determine the subject of evidence, establish legal presumptions, which directly affects the division of duties for proof. Normative settlement as a compulsory feature of judicial evidence does not cause debate in law, however, when defining the concept of proof, this aspect is not taken into account by all researchers. Secondly, the proof is a combination of the mental and procedural (practical) activity of the subjects of proof, which are in constant dialectical interaction, and it is impossible to separate them. Of course, the mental process can not be regulated by the rules of law, but if the judge considers beyond legal and practical categories, the court decision will not be legal and justified and subject to cancellation. The interaction of mental and practical activity concerns not only the court, but also the persons involved in the case: the plaintiff and the defendant, performing their duties on proving, taking part in the study of evidence, on the one hand, obey the law, on the other - the logic of his thinking. Judicial proof is a sort of «place of meeting» of logic and legal activity, the combination of means and methods of scientific knowledge, developed in the classical formal logic, is a special theoretical method of knowledge, which is one of the grounds of legal knowledge and activities.